Rethinking the Public Sphere Through Transnationalizing Processes
XVI, 296 p.
Keywords: This book discusses the extent to which the theoretical relevance and analytical rigor of the concept of the public sphere is affected by current processes of transnationalization. The contributions address fundamental questions concerning the viability of a socially and politically effective public sphere in a post-Westphalian world.